Bevacizumab Attenuates Hepatic Fibrosis in Rats by Inhibiting Activation of Hepatic Stellate Cells - Huang, Yangqing (Public Library of Science, 2013)
Angiogenesis is a fundamental part of the response to tissue injury, which is involved in the development of hepatic fibrosis. Vascular endothelial growth factor plays an important role in angiogenesis. The expression of VEGF is increased during hepatic fibrogenesis and correlates with the micro-vessel density. In this study, we investigated the effects of bevacizumab, an anti-angiogenetic drug, on the formation of hepatic fibrosis. We found that bevacizumab could attenuate the development of hepatic fibrosis and contribute to the protection of liver function. Bevacizumab was also found to downregulate the expression α-SMA and TGF-β1, which have been reported to be profibrogenic genes in vivo. We also observed that the expression of VEGF increased significantly during the development of hepatic fibrosis and CCl(4) was found to induce hepatocytes to secrete VEGF, which led to the activation and proliferation of HSCs. Bevacizumab was also found to block the effects of the hepatocytes on the activation and proliferation of HSCs. Our results suggest that bevacizumab might alleviate liver fibrosis by blocking the effect of VEGF on HSCs. Bevacizumab might be suitable as a potential agent for hepatic fibrosis therapy.